Deep digital poetry: Interrogating Tiv oral poetry within postmodernity - Ikyer, Godwin Aondaofa (Tydskrif vir Letterkunde, 2017)
Poetry is one of the most vibrant artistic forms for socio-economic and political reconstruction of society among the Tiv of North Central Nigeria. The poets fix themselves in the forefront of arousing and propagating cultural consciousness, exposing vices, extolling virtues and personalities with such attributes, mobilizing people for unity and development, ensuring progressive change, maintaining social order and cohesion, unmasking socio-economic contradictions of class and polity, expressing the unheard voices of the voiceless in society and charting out a direction for the future of society. By reflecting the jeers, fears, aspirations, visions and general character of the society, they occupy a popular place and position in the social structure of Tiv society and their poetry is reinvigorated, in the usual popular way, in the new sensibilities of the digital technology being they dynamic in thematic exploration, traditional or modern. This article presents an exploratory overview of Tiv poetry in its changing digital forms of "secondary orality" which not only preserve the material but transform its productive, aesthetic and performance bounds to unending digital spaces creating in the wake a new character, a special effect, a new transmitting and storage pattern and the commodification of an individual's creations. The paper finally locates digi-orature, this new way of interrogating oral poets and their creations, within the ambience of postmodernity capable of attracting audiences outside the Tiv linguistic and geographical space.